Inequities in Noncommunicable Diseases - Valerie Gilbert T. Ulep; Danica Aisa P. Ortiz; John Juliard Go; Charmaine Duante; Rosa C. Gonzales; Laurita R. Mendoza; Clarissa Reyes; Frances Rose Elgo; Melanie P. Aldeon (Philippine Institute for Development Studies (PIDS), 2012)
This report presents the findings of the research conducted by the Philippine Institute for Development Studies (PIDS) on leading noncommunicable diseases (NCDs). With the collaborative efforts of the World Health Organization (WHO) and Food and Nutrition Research Institute (FNRI), this research project was conducted to supplement the Department of Health's (DOH) initiative in crafting a national strategy in the prevention and control of noncommunicable diseases.This study presents evidences on mortality, morbidity, some social determinants, and inequities. Different secondary data sets like the National Nutrition Survey, National Demographic and Health Survey, Death Registry from the National Statistics Office, Family Income and Expenditure Survey and other information obtained from other studies were analyzed to come up with a unified and comprehensive study that depicts the true picture of NCDs epidemic in the country.
Keywords: 330; Philippines; noncommunicable diseases; cardiovascular diseases; cancer; diabetes mellitus; risk factors; social determinants; inequity; Herzkrankheit; Krebskrankheit; Diabetes; Gesundheitsrisiko; Soziale Lage; Soziale Ungleichheit; Philippinen